Functional Flows in Groundwater-Influenced Streams: Application of the California Environmental Flows Framework to Determine Ecological Flow Needs - Yarnell, Sarah M.; Willis, Ann; Obester, Alyssa; Peek, Ryan A.; Lusardi, Robert A.; Zimmerman, Julie; Grantham, Theodore E.; Stein, Eric D. (Frontiers in Environmental Science, 2022)
Environmental flows, or the practice of allocating water in river systems for ecological purposes, is a leading strategy for supporting aquatic species and improving river health. However, consideration of surface-groundwater connectivity is seldom addressed in environmental flow development due to a lack of methodologies that account for groundwater contributions to instream flow. Groundwater-influenced streams and their associated groundwater dependent ecosystems (GDEs) have been identified as key refugia for native biota under a rapidly changing climate. These ecosystems are anticipated to be more resistant to climate change because groundwater input buffers the adverse effects of low flows and high temperatures, particularly in the dry season. Less understood, however, is the relative contribution of groundwater inputs to streamflow and how these surface-groundwater water interactions should be accounted for in environmental flow assessments and management actions. In order to assess ecological flow needs in groundwater-influenced streams, we applied the California Environmental Flows Framework (CEFF) in two river systems in California, USA. The Little Shasta River and the lower Cosumnes River are representative of many groundwater-influenced streams throughout the semi-arid western United States. Historically, perennial streamflow once sustained diverse native aquatic species in these ecosystems, but now streamflow supports agricultural development resulting in periodic stream dewatering. We found CEFF was useful in quantifying ecological flow needs for seasonal components of the flow regime that support ecosystem functionality. In particular, CEFF offered flexibility to incorporate information on the seasonal and spatial dimensions of groundwater influences in the development of ecological flows. The focus on ecosystem functions in CEFF, and ability to account for groundwater influences on those functions, creates opportunities for integrated surface-groundwater management strategies that support the recovery and protection of streamflows in groundwater-influenced streams.